Buddhism and politics in twentieth-century Asia - Harris, Ian Charles (Pinter, 1999)
In this study, a team of international scholars assess the manner in which Buddhist organizations and individuals have resisted, come to terms with, or in some cases allied themselves with the forces of war, modernity, westernization, nationalization, capitalism, communism, and ethnic conflict. By examining issues such as left-right divisions in the monastic order, the rise of organized lay movements, Buddhist social activism, as well as explicitly Buddhist inspired political activity, this book seeks to demonstrate that the emphasis on meditation and mental training is only one strand in this.